Solar Synthesis Gas Production via the Thermochemical Cerium Oxide Redox Cycle: Inert-Swept and Methane-Hybridized Reduction - Krenzke, Peter (My University, 2016)
The cerium oxide (ceria) redox cycle is evaluated as a means for producing synthesis gas from carbon dioxide and water using solar energy. Two options are considered for facilitating oxygen removal during ceria reduction: inert gas sweeping and reaction with methane to produce synthesis gas. Thermodynamic process analyses are developed to ascertain the viability of the cycle and identify requirements for high efficiency under the assumption of equilibrium chemistry. A parametric experimental study is conducted to determine the impact of temperature and methane flow rate on methane conversion, syngas selectivity, oxidizer conversion, and the solar-to-fuel efficiency.
University of Minnesota Ph.D. dissertation. January 2016. Major: Mechanical Engineering. Advisor: Jane Davidson. 1 computer file (PDF); xii, 103 pages.
Keywords: ceria; hydrogen; methane; renewable fuels; solar; synthesis gas